2022
DOI: 10.1186/s12967-022-03461-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatments of chronic fatigue syndrome and its debilitating comorbidities: a 12-year population-based study

Abstract: Background This study aims to provide 12-year nationwide epidemiology data to investigate the epidemiology and comorbidities of and therapeutic options for chronic fatigue syndrome (CFS) by analyzing the National Health Insurance Research Database. Methods 6306 patients identified as having CFS during the 2000–2012 period and 6306 controls (with similar distributions of age and sex) were analyzed. Result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…After checking the widely used the HAMA and HAMD (Zhang et al, 2020;Zimmerman et al, 2020), we observed that the data from the HAMA, HAMD, and SCL-90 exhibited distinct trends regarding the assessment of emotional disorders (Figure 5). This confirmed that most patients with CFS had anxiety (69.5%) and depression (79%) according to HAMA and HAMD, suggesting that people with CFS have a high rate of comorbidity with anxiety/ depression (Leong et al, 2022). While many patients experience noticeable mental symptoms like anxiety or depression, they tend to perceive their condition primarily in terms of physical problems.…”
Section: Discussionsupporting
confidence: 59%
“…After checking the widely used the HAMA and HAMD (Zhang et al, 2020;Zimmerman et al, 2020), we observed that the data from the HAMA, HAMD, and SCL-90 exhibited distinct trends regarding the assessment of emotional disorders (Figure 5). This confirmed that most patients with CFS had anxiety (69.5%) and depression (79%) according to HAMA and HAMD, suggesting that people with CFS have a high rate of comorbidity with anxiety/ depression (Leong et al, 2022). While many patients experience noticeable mental symptoms like anxiety or depression, they tend to perceive their condition primarily in terms of physical problems.…”
Section: Discussionsupporting
confidence: 59%
“…Research findings indicate a significantly higher incidence of mood and anxiety disorders among individuals with CFS/ME compared to those without functional somatic syndromes. Furthermore, the prevalence of these mental problems tends to be higher in CFS/ME compared to FM and irritable bowel syndrome (Daniels et al, 2017; Janssens et al, 2015; Leong et al, 2022). In this line, the present sample showed in average a moderate level of anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Integrating biofeedback into exercise, massage, and physical therapy programs results in greater improvements in pain, mobility, and quality of life versus either therapy alone for musculoskeletal pain, temporomandibular joint disorders, irritable bowel syndrome, chronic fatigue syndrome, and pelvic pain [299][300][301][302][303][304] (Additional file 1: Fig. S4).…”
Section: Biofeedbackmentioning
confidence: 99%